Effect of some macro elements Ca N P K on the quantitative and qualitative characteristics of the fruits A Review (Texas Journal of Multidisciplinary Studies, 2021)
The availability of good and vigorously growing varieties is one of the most important means of spreading and developing fruit cultivation, and this requires adequate care, especially in terms of fertilization, as it drains a lot of nutrients from the ground for use in various vital activities. And the appropriate amount, due to the positive effect of the fertilization process on the growth of seedlings and trees and their early entry into the fruiting stage. Among these fertilizers are the major elements that we will talk about the importance of some of them in this article and their role in the quantitative and qualitative characteristics of fruit trees